Menyuarakan Hak tanpa Sekat: Sebuah Ekspresi Gerakan Sosial Petani - Izudin, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2019)
This paper highlighted the social change of peasant in the process of facing any struggling movement. Applying a qualitative method and case study approach, the data in this research were collected by observation, interview, and document study. The data were analyzed using the theory of â€œSocial-Economic Moralityâ€. By analyzing the data using this theory this article revealed the changing society in terms of peasant political attitude. This research found three important aspects. Firstly, compromise is a kind of strategy applied by peasants in their movement. Because there are no supporting factors for peasants to avoid the stateâ€™s hegemony and exploitation, so the only strategy to deal with the expansive tendency of capitalism is by changing the political attitude of peasants. Secondly, the organizational consolidation is claiming peasantâ€™s rights. Thirdly, capacity development through the empowerment process is a form of compromise way of peasantsâ€™ movement. These three compromise models are the ways to avoid conflict to escalate.